El futuro no es más lo que era. La tecnología y la gente en tiempos de internet de Horacio C. Reggini. Educa, 2005, Buenos Aires, 450 pp. - Muñarriz, Matías A. (2005)
Fil: Muñarriz, Matías A. Universidad Austral; Argentina